OMEx-diesel blends as high reactivity fuel for ultra-low NOx and soot emissions in the dual-mode dual-fuel combustion strategy. (1st September 2020) - García, Antonio; Gil, Antonio; Monsalve-Serrano, Javier; Lago Sari, Rafael
Highlights: Diesel-OMEx blends with 0%, 50%, 70% and 100% OMEx content by mass are tested. EURO VI NOx and soot limits achieved with OMEx independently on the engine load. Blends with 70% OMEx content allow to fulfill the EUVI limits up to 80% engine load. Abstract: Previous works demonstrated that the use of Oxymethylene ether (OMEx) in advanced combustion modes, as the dual-mode dual-fuel combustion, leads to a notable reduction of the lifecycle CO2 emissions while promoting lower NOx and soot emissions than those from conventional diesel combustion. Nonetheless, the low heating value of OMEx results in a fuel consumption increase. A possible solution to avoid this drawback is by blending OMEx with diesel fuel. This will help to introduce the OMEx in the market with minimum changes in the infrastructure. In this context, this work evaluates the impact of using OMEx-diesel blends in different mass percentages (50% and 70% of OMEx in diesel), compared to the reference net fuels (net diesel and OMEx) in a multi-cylinder compression ignition engine operating under dual-mode dual-fuel combustion at different engine loads (25%, 50%, 80% and 100%) and 1800 rpm. At each condition, an air mass sweep was performed to assess the limiting operating conditions with each fuel due to either excessive pressure gradients and soot production, or low combustion efficiency. The results suggested that the OMEx-diesel blends allow to reduce the soot emissions compared to net diesel for all the conditions tested. In addition, blends having an OMEx mass content greater than 70% allowed to fulfill the EUVI limits for NOx with ultra-low soot levels (<0.01 g/kWh) up to 80% engine load. Nonetheless, the unique fuel able to achieve the EUVI limit for NOx with zero soot emissions simultaneously at 100% of engine load was found to be the pure OMEx.